US vs China Rivalry in the Biden Era by Bambang Cipto - Sidik Jatmika (WIMAYA, 2022)
This book provides a thorough analysis of the dynamics of international relations between the United States and China during the first term of Joe Biden's presidency. In his book, Cipto makes the case that the United States has to be more cautious while preserving its relationship with China, particularly during the Biden administration when it is important to protect both domestic and global interests. As the subsequent president of the United States, Joe Biden exercised prudence when dealing with China in a new rivalry. Biden has specific demands to improve the role of the United States in the international world after being considered to have experienced a setback in the era of Donald Trump's leadership with his "America First" policy. In addition, Donald Trump openly launched a trade war strategy with China which increased tensions between the two countries. The efforts made by Joe Biden can be likened to the efforts of “Rambo”, a fictional character who represents United States patriotism in “cleaning up” all forms of international threats. But this time what they faced was not an ordinary threat, this special thread can be reimagined as a dragon that had just awakened and could pounce at any time and turn terrifying. Therefore, instead of using firearms blindly as the films illustrate, Rambo must be able to dance beautifully to face the rise of the dragon.